A Miniaturized Broadband 1 × 4 Filtering Butler Matrix With 360° Continuous Progressive Phase Shift and Simplified Control - Wei, Liu-Yu; Chen, Fu-Chang; Wang, Xi-Zhu (IEEE transactions on microwave theory and techniques, 2025)
This article presents a novel, miniaturized 1 × 4 filtering Butler matrix (BM) that provides 360° continuous progressive phase shift with a simplified control mechanism for broadband applications. The proposed filtering BM, which comprises a power-division module, a fixed-phase shift module, and a continuous-phase shift module, is based on a 1 × 4 BM topology with two integrated single-pole-double-throw (SPDT) switches in place of a single-pole-four-throw (SP4T) switch in conventional design for miniaturization. The use of conductor-backed coplanar waveguide (CB-CPW)-based crossovers in the fixed-phase shift module enables a reduction in size, an enhancement in isolation, and an improvement in the balance of the output amplitude. To realize a 360° continuous progressive phase shift and a filtering frequency response, two phase shifters (PSs) with a continuous phase shift of 135^{° } ~± ~8^{° } are used in the power-division module and four filtering phase shifters (FPSs) with 90^{° } ~± ~5^{° } continuous phase shift are used in the continuous-phase shift module. The FPSs which are based on a composite right/left-handed transmission line (CRLH-TL) and coupled resonators demonstrate good out-of-band suppression performance when phase shifting. The combination of the three modules results in the formation of a 1 × 4 BM operating at 2.1-2.7 GHz, which offers a 360° continuous phase shift and a filtering frequency response. The simulated and measured results demonstrate the validity of this design method for continuous tunable 360^{° } ~1 × 4 filtering BM.